2020
DOI: 10.1002/asi.24415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting future research impact at different career stages—A social network perspective

Abstract: Performance assessment is ubiquitous and crucial in people analytics. Scientific impact, particularly, plays a significant role in the academia. This paper attempts to understand researchers' career trajectories by considering the research community as a social network, where individuals build ties with each other via coauthorship. The resulting linkage facilitates information flow and affects researchers' future impact. Consequently, we systematically investigate the career trajectories of researchers with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 79 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…In terms of the characteristics of authors, studies have shown that authors of different ages have different citation behaviors (Costas & Bordons, 2011 ; Costas et al, 2012 ). The physical age reflects the author’s career stage which has been found to affect scientific integrity (Fanelli et al, 2015 ), knowledge recency (Liang et al, 2020 ), work meaningfulness (Lopez & Ramos, 2017 ), future research impact (Zuo & Zhao, 2021 ), publication and scientists’ satisfaction (Husemann et al, 2017 ). Whether there are differences in clinical translation intensity in the papers published by authors at different career stages needs to be further examined.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the characteristics of authors, studies have shown that authors of different ages have different citation behaviors (Costas & Bordons, 2011 ; Costas et al, 2012 ). The physical age reflects the author’s career stage which has been found to affect scientific integrity (Fanelli et al, 2015 ), knowledge recency (Liang et al, 2020 ), work meaningfulness (Lopez & Ramos, 2017 ), future research impact (Zuo & Zhao, 2021 ), publication and scientists’ satisfaction (Husemann et al, 2017 ). Whether there are differences in clinical translation intensity in the papers published by authors at different career stages needs to be further examined.…”
Section: Methodsmentioning
confidence: 99%
“…This focus is a welcome and long overdue antidote to publication counts, which, although used by some hiring committees and science evaluators, have been repeatedly criticised by interdisciplinary and international scholars for being a poor certification of scientific merit (e.g. Trenchard, 1992;Feller, 2004;Zuo & Zhao, 2021). Prinz et al (2021) established the most successful female educational psychologists through an open call for nominations via social media of two key professional networks.…”
Section: What Is Academic Success?mentioning
confidence: 99%
“…One group includes metadata relations such as authorship, co-authorship, and citations [49,43]. Research in this group has focused mainly on examining the social dimension of scholarly communications, such as research impact assessments [36,40,18,10,12,34,46,56], co-author prediction [43,47,20,51,37] and scholarly community analysis [49]. Popular data resources that have been explored in this group include Microsoft Academic Graph [42] and PubMed [1].…”
Section: Relations Mined From Scientific Publicationsmentioning
confidence: 99%